1999
DOI: 10.1143/jjap.38.l780
|View full text |Cite
|
Sign up to set email alerts
|

Phase- and Wall-Locked Modes Found in a Large Reversed-Field Pinch Machine, TPE-RX

Abstract: We studied the electrophoretic migration of electrophoretic inks by measuring the total reflection at the interface between the electrode and the ink solvent simultaneous with the current response to a cyclic-polarity-reversed triangular voltage. We demonstrated that the current peaks and optical responses to the cyclic-polarity-reversed triangular voltage are effective for the easy evaluation of mobility, the charge amount of ions and ink particles, and the interactions of particles with the electrode and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…[15][16][17]23 In MST, the dynamo modes, which are responsible for generating the reversed magnetic field, continually exhibit a sawtooth behavior as a function of time 2 as shown in Fig. 1.…”
Section: A Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17]23 In MST, the dynamo modes, which are responsible for generating the reversed magnetic field, continually exhibit a sawtooth behavior as a function of time 2 as shown in Fig. 1.…”
Section: A Previous Workmentioning
confidence: 99%
“…21 Phase-locked modes were almost always observed to lock to the wall in close proximity to the poloidal gap. ͑Reversed-field pinch devices have a characteristic set of insulating intersecting gaps cutting the vacuum chamber in the toroidal and poloidal directions.͒ In another RFP experiment TPE-RX, 16 it has been suggested that the locking phenomenon may be due 16 to the braking effect of eddy currents induced in the vacuum vessel by the growing, phase-locked modes. In addition, it was also proposed that locking is enhanced by the presence of a ''halo'' current, which is the current that flows through the plasma ''scrape-off'' layer into the vacuum chamber at the locking location.…”
Section: B the Slinky Modementioning
confidence: 99%
“…In MST, another large RFP machine, the mode is locked to the wall only when the induced field error exceeds a certain percentage of the poloidal magnetic field at the plasma surface [8]. A locked mode phenomenon quite similar to RFX is observed in TPE-RX [9,10]. The toroidal distribution of the radial magnetic fluctuation shows a toroidally localized bumpy structure locked at the same place throughout the discharge.…”
Section: Introductionmentioning
confidence: 95%
“…Locked mode phenomena have been studied in many RFP machines, but the detailed mechanism for the locked mode is not yet well understood [7][8][9][10]. It is speculated that the locked mode influences the global confinement properties by interacting with the first wall.…”
Section: Introductionmentioning
confidence: 99%
“…In the TPE-RX experiment [9], it was found under certain experimental conditions that the probability of locking decreased by 25% by lowering the plasma current I P , decreasing the plasma current rise time, and decreasing the filling pressure of the deuterium gas.…”
Section: Introductionmentioning
confidence: 99%